The Impact of COVID-19 Outbreak in Italy on the Sustainable Food Consumption Intention From a “One Health” Perspective - Castellini, Greta; Savarese, Mariarosaria; Graffigna, Guendalina (Frontiers in Nutrition, 2021)
Coronavirus disease (COVID-19) is a transmissible illness that was recognized in December 2019 and World Health Organization (WHO) stated a pandemic on 11 March 2020. As no cure has been developed for COVID-19 disease yet, Italy has adopted restrictive measures to avoid the spread of the virus, causing different psychological reactions (e.g. stress, anxiety) that lead people to change lifestyle and in particular the consumer orientation towards food. In addition, the COVID-19 emergency had also affected the Italian economy, causing an 11.3% decrease in GDP (gross domestic product). All these changes gave rise to a sense of instability, but it is known that new possibilities may arise in these situations. In particular, the pandemic could be the turning point to make consumers aware of the close link between human health and the ecosystems, supporting the “One Health” perspective and enhancing the orientation to consumer sustainable food products. However, little is known about how the psychological reactions to COVID-19 emergency have affected the consumers’ intention to purchase sustainable food products. In order to answer these questions, a representative sample of 1004 Italian citizens, extracted by stratified sampling, answered an online survey between May the 12th -18th 2020. The data were analyzed using ANOVA and contingency tables. The results show that during phase one of COVID-19 disease about 30% of the sample have frequently consumed the certified sustainable food products and about 20% of the sample have intention to increase the consumption of them in the next six months, percentages that increase among those who feel more vulnerable regarding the risk contagion. Moreover, the psychological impact of the COVID-19 emergency has led to a change in consumers’ attitudes, increasing the interest in animal and environmental issues, in personal health, and the sense of personal responsibility, aspects that drive the future purchase sustainable food products. This research highlights how the psychological reactions to the health emergency have changed the consumers’ attitudes towards sustainability issues, leading them to follow a sustainable diet that is recognized as a way to preserve the food and nutrition security and the healthy life for present and future generations.